2022
DOI: 10.3892/ijo.2022.5401
|View full text |Cite
|
Sign up to set email alerts
|

lncKRT16P6 promotes tongue squamous cell carcinoma progression by sponging miR‑3180 and regulating GATAD2A expression

Abstract: Tongue squamous cell carcinoma (TSCC) is characterized by a poor prognosis and its 5-year overall survival rate has not improved significantly. However, the precise molecular mechanisms underlying TSCC remain largely unknown. Through RNA screening, the present study identified a novel long noncoding RNA (lncRNA), keratin 16 pseudogene 6 (lncKRT16P6), which was upregulated in TSCC tissues and cell lines and associated with TSCC tumor stage and differentiation grade. Inhibition of lncKRT16P6 expression reduced T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Additionally, hsa-miR-4492, the seventh most upregulated miRNA in our study, is frequently silenced by lncRNAs in ovarian and bladder cancer, specifically FOXD2-AS1 and LINC00319, respectively, which thus promotes proliferation, migration, and invasion [72,73]. Meanwhile, hsa-miR-3180, the tenth most upregulated miRNA in our study, is modulated by lncKRT16P6 in tongue squamous cell carcinoma [74] and by SNHG17 in hepatocellular carcinoma [75]. Furthermore, hsa-miR-3180 has been shown to be a critical regulator involved in de novo fatty acid synthesis and uptake in HCC [76].…”
Section: Discussionmentioning
confidence: 48%
“…Additionally, hsa-miR-4492, the seventh most upregulated miRNA in our study, is frequently silenced by lncRNAs in ovarian and bladder cancer, specifically FOXD2-AS1 and LINC00319, respectively, which thus promotes proliferation, migration, and invasion [72,73]. Meanwhile, hsa-miR-3180, the tenth most upregulated miRNA in our study, is modulated by lncKRT16P6 in tongue squamous cell carcinoma [74] and by SNHG17 in hepatocellular carcinoma [75]. Furthermore, hsa-miR-3180 has been shown to be a critical regulator involved in de novo fatty acid synthesis and uptake in HCC [76].…”
Section: Discussionmentioning
confidence: 48%
“…For example, it has been reported that lncRNA 01614 promoted pancreatic cancer progression by suppressing GSK-3β (12). Zhang et al (13) reported that LncKRT16P6 promoted tongue squamous cell carcinoma progression by functioning as a competing endogenous RNA. In prostate cancer, the majority of previous studies have paid attention to the effects of lncRNAs on the proliferation and metastasis of cancer cells (10,14,15), while the expression patterns and functions of lncRNAs in the progression from HSPC to CRPC remain overlooked.…”
Section: Vim-as1 Promotes Proliferation and Drives Enzalutamide Resis...mentioning
confidence: 99%
“…Decoy lncRNAs function as decoys of transcription factors or competing endogenous RNAs (ceRNAs) to trap miR-NAs and reverse their inhibitory effect in mRNA translation. In tongue squamous cell carcinoma, lncKRT16P6 acts as a trap for binding miR-3180 to promote the expression of GATA zinc finger domain containing 2A (GATAD2A), thus leading to tumorigenesis and metastasis [32]. Highly expressed lncRNA MALAT1 promotes tumor cell migration and invasion by sinking miR-384 in glioma [33].…”
Section: Introductionmentioning
confidence: 99%